EVIDENCE OF COUNTER-DIFFERENCE SURFACE HEAT FLUXES AND ITS HYPOTHESES - Edi Santoso (Jurnal Sains & Teknologi Modifikasi Cuaca, 2001)
Parameterization of surface heat flux estimates near-surface turbulent heat fluxes fromdifferences of potential temperature between the surface skin and the mid-mixed layer(ML). The rate of this turbulent transport is proportional to the product of a convectivevelocity times an empirical transport coefficient. New data from three different siteswithin Boundary Layer Experiment - 1996 (BLX96) are used to evaluate surface heatflux parameterization. Old data from six other field programs (BLX83, Koorin, FIFE,Monsoon 90, HAPEX-MOBILHY, and TOGA-COARE) are re-analyzed to test thisparameterization. Evidence from virtually all of these experiments indicates that theempirical transport coefficient for heat fluxes ( C* H ) does not depend on surfaceroughness. Positive turbulent heat fluxes are observed to exist near the bottom of theML even when there is zero potential temperature difference ( âˆ†Î¸ =0) between thesurface skin and the mid-ML. Evidence suggests that positive heat fluxes could alsooccur when the surface skin has a slightly colder potential temperature than the mid-ML, implying a flux that is opposite or counter to the potential-temperature difference.Such counter-difference fluxes could be explained by an infrared radiative transferfrom the surface skin, or by non-equilibrium conditions during rapidly-changinginsolation near sunset.Fluks panas turbulen dekat permukaan dapat diestimasi dari selisih antara suhupotensial di batas permukaan (surface skin) dan di bagian tengah lapisan tercampur(mid-mixed layer). Kecepatan dari transpor turbulen ini sebanding dengan perkalianantara koefisien empiris transpor dengan kecepatan konvektif. Data baru dari hasilpengukuran BLX96 pada 3 lokasi yang berbeda akan digunakan untuk mengevaluasiparameterisasi ini. Sementara data yang diperoleh dari yang pernah dilakukansebelumnya (BLX83, Koorin, FIFE, Monsoon 90, HAPEX-MOBILHY, and TOGA-COARE) digunakan untuk menguji hasil parameterisasi ini. Hasil yang diperolehmengindikasikan bahwa koefisien empiris transpor untuk fluks panas tidak tergantungpada kekasaran permukaan (surface roughness). Bukti juga menunjukkan bahwafluks panas positif dapat terjadi ketika suhu potensial di surface skin sama atau sedikitlebih dingin daripada di mid-mixed layer. Kejadian seperti ini, disebut counter-difference fluxes, dapat dijelaskan dengan tranfer radiasi infra merah dari surface skinatau dengan kondisi ketidaksetimbangan perubahan secara cepat insolasi saatmendekati matahari terbenam.